2005
DOI: 10.4141/a04-008
|View full text |Cite
|
Sign up to set email alerts
|

Mare milk nitrogen fractions during lactation and determination by reversed-phase HPLC of the major whey proteins

Abstract: P. 2005. Mare milk nitrogen fractions during lactation and determination by reversed-phase HPLC of the major whey proteins. Can. J. Anim. Sci. 85: 93-99. The aim of this research was to describe the changes of the nitrogen fractions in milk of Haflinger nursing mares and in particular to determine the whey protein content and distribution, and their evolution throughout the first 6 mo of lactation. Samples were collected by hand-milking on days 4, 20, 40, 60, 80, 120, 150 and 180 post-partum. Nitrogen fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The protein content decreases by 20e25% from d 28 to d 150 in horse (Doreau & Martin-Rosset, 2011;Mariani et al, 2001;Martuzzi, Summer, Formaggioni, & Mariani, 2004;Summer, Tirelli, Formaggioni, Malacarne, & Mariani, 2005;Ullrey, Struthers, Hendricks, & Brent, 1966) and donkey milk (Giosuè et al, 2008;Guo et al, 2007;Salimei et al, 2004a). In equids, the milk nitrogen fractions are also reported to be influenced by the length of the lactation period.…”
Section: Gross Composition and Energy Contentmentioning
confidence: 93%
See 1 more Smart Citation
“…The protein content decreases by 20e25% from d 28 to d 150 in horse (Doreau & Martin-Rosset, 2011;Mariani et al, 2001;Martuzzi, Summer, Formaggioni, & Mariani, 2004;Summer, Tirelli, Formaggioni, Malacarne, & Mariani, 2005;Ullrey, Struthers, Hendricks, & Brent, 1966) and donkey milk (Giosuè et al, 2008;Guo et al, 2007;Salimei et al, 2004a). In equids, the milk nitrogen fractions are also reported to be influenced by the length of the lactation period.…”
Section: Gross Composition and Energy Contentmentioning
confidence: 93%
“…In equids, the milk nitrogen fractions are also reported to be influenced by the length of the lactation period. The casein content declines by approximately 20e30% in horse (Mariani et al, 2001;Martuzzi et al, 2004;Summer et al, 2005) and donkey milk (Fantuz, Maglieri, Varisco, La Manna, & Salimei, 2009b;Giosuè et al, 2008) while results on the non-protein nitrogen (NPN) milk content during lactation are not conclusive. No significant trends are reported for horse milk NPN by Mariani et al (2001) and Summer et al (2005) but not by Martuzzi et al (2004), who observed a significant decline during lactation, consistent with reports by Guo et al (2007) for donkey milk.…”
Section: Gross Composition and Energy Contentmentioning
confidence: 96%
“…However, it should be underlined that noticeable differences in equine milk α-LA occur between various investigations. For example, in a study by Summer et al (2005) the mean concentration of α-LA was 1.6 g/l, while in the experiment by Markiewicz-Kęszycka et al (2013) this protein was more abundant (2.2 g/l). Moreover, a significant variability in α-LA content was observed between various mares analysed in the same study.…”
Section: Introductionmentioning
confidence: 90%
“…It seems that selected equine LGB gene variants can be considered potential markers for these particular traits; however, further studies with larger animal groups of different horse breeds are necessary. Associations between β-lactoglobulin polymorphisms and total milk protein and/or fat concentration have previously been described for cattle [12,42,43] and sheep [44,45]. We have also recorded a relationship between genotypes in rs1151091548 (LGB1) and rs1147750066 (LGB2) SNPs and the milk lactose level of PPH and PCH mares, respectively.…”
Section: Discussionmentioning
confidence: 86%
“…However, some different values have been found by different investigations. For example, Summer et al (2005) [12] found the mean concentration of LGB in equine milk to be 2.8 g L -1 , while Markiewicz-Kęszycka et al (2013) [13] recorded a slightly lower value (2.6 g L -1 ).…”
Section: Introductionmentioning
confidence: 96%